Espectrometria de massas de alta resolução acoplada a espectrometria mobilidade iônica para análise de matrizes complexas - Tose, Lilian Valadares (2018)
Mass spectrometry (MS) is a technique able to ionize simple molecules until complex structures, performing efficiently and dynamically with a wide application using high sensitivity and speed of analysis. Although MS hasconsiderable interest in the scientific society, the application of new technologies in the field of complex matrix analysis still is little explored.Inanalyzes of crude oil, paraffin and condensed aromatic standards, the atmospheric solids analysis probe mass spectrometry (ASAP-MS) is a powerful ionization sourceforcharacterization of samples in original form. Initially, two methodologies were used to determine the chemical composition of the samples: (1) using a temperature gradient ranging from 150 to 600 °C at a heating rate of 150 °C.min-1(parafina) or 50 °C.min-1; (2) with a constant temperaturearound350 °C. ASAP(+)-MS ionized crude oil and paraffin, showing a typical petroleum profile in the range of m/z200 -1400 for both samples. This performancecould relateASAP sourceto detection of compounds of high molecular weight (> 1000 Da). In addition, the AC standardswere identifiedin two ionicforms: radicals, [M]+•and protonated cations, [M+H]+, with minimal fragmentation. Therefore, ASAP was efficient for accessing the chemical composition of polar and non-polar compounds.Analysis of the Cannabis sativaL. plant, were doing by ultra-high performance liquid chromatography coupled to travelingwave ionic mass spectrometry (UPLC-TWIMS MS) using electrospray ionization source in both modes, ESI (±). Hashish, marijuana, and parts of the plant Cannabis sativaL. (flower and leaf) were analyzed. Isomeric compounds were identified inacomplex mixture of cannabinoids, mainly ?9-THC, cannabidiol (CBN-C5and Mw= 310 Da), ?9-tetrahydrocannabinolic acid A and B (?9-THCA-C5A/B and Mw= 358 Da) and their isomers. Analizes by ESI-TWIMSMS were identified three isomers, m/z315/313, 311, and 357, while a high selectivity was observedin UPLC-ESI-TOF MS data, identifying more thanfour isomeric compounds in the single ion acquisition mode (SIM).In other study, we evaluated the use of a high resolution mobility analyzer coupled to ultra high resolution mass spectrometry for molecular characterization of dissolved organic matter. The main goal wastovalidate the reproducibility of trapped ion mobility spectrometry (TIMS), the range of applicability and possible challenges during routine analysis.TIMS coupledto TOF MS and FT-ICR MS showed similar 18performance and high reproducibility. For the analysis of complex mixtures, both platforms were able to aquiriedthe main characteristics. However, the increase ofchemical complexity at nominal mass level (m/z> 300-350), only TIMS-FT-ICR MS was able to solve the compositional tendencies of lower Mass spectrometry (MS) is a technique able to ionize simple molecules until complex structures, performing efficiently and dynamically with a wide application using high sensitivity and speed of analysis. Although MS hasconsiderable interest in the scientific society, the application of new technologies in the field of complex matrix analysis still is little explored.Inanalyzes of crude oil, paraffin and condensed aromatic standards, the atmospheric solids analysis probe mass spectrometry (ASAP-MS) is a powerful ionization sourceforcharacterization of samples in original form. Initially, two methodologies were used to determine the chemical composition of the samples: (1) using a temperature gradient ranging from 150 to 600 °C at a heating rate of 150 °C.min-1(parafina) or 50 °C.min-1; (2) with a constant temperaturearound350 °C. ASAP(+)-MS ionized crude oil and paraffin, showing a typical petroleum profile in the range of m/z200 -1400 for both samples. This performancecould relateASAP sourceto detection of compounds of high molecular weight (> 1000 Da). In addition, the AC standardswere identifiedin two ionicforms: radicals, [M]+•and protonated cations, [M+H]+, with minimal fragmentation. Therefore, ASAP was efficient for accessing the chemical composition of polar and non-polar compounds.Analysis of the Cannabis sativaL. plant, were doing by ultra-high performance liquid chromatography coupled to travelingwave ionic mass spectrometry (UPLC-TWIMS MS) using electrospray ionization source in both modes, ESI (±). Hashish, marijuana, and parts of the plant Cannabis sativaL. (flower and leaf) were analyzed. Isomeric compounds were identified inacomplex mixture of cannabinoids, mainly ?9-THC, cannabidiol (CBN-C5and Mw= 310 Da), ?9-tetrahydrocannabinolic acid A and B (?9-THCA-C5A/B and Mw= 358 Da) and their isomers. Analizes by ESI-TWIMSMS were identified three isomers, m/z315/313, 311, and 357, while a high selectivity was observedin UPLC-ESI-TOF MS data, identifying more thanfour isomeric compounds in the single ion acquisition mode (SIM).In other study, we evaluated the use of a high resolution mobility analyzer coupled to ultra high resolution mass spectrometry for molecular characterization of dissolved organic matter. The main goal wastovalidate the reproducibility of trapped ion mobility spectrometry (TIMS), the range of applicability and possible challenges during routine analysis.TIMS coupledto TOF MS and FT-ICR MS showed similar 18performance and high reproducibility. For the analysis of complex mixtures, both platforms were able to aquiriedthe main characteristics. However, the increase ofchemical complexity at nominal mass level (m/z> 300-350), only TIMS-FT-ICR MS was able to solve the compositional tendencies of lower aMass spectrometry (MS) is a technique able to ionize simple molecules until complex structures, performing efficiently and dynamically with a wide application using high sensitivity and speed of analysis. Although MS hasconsiderable interest in the scientific society, the application of new technologies in the field of complex matrix analysis still is little explored.Inanalyzes of crude oil, paraffin and condensed aromatic standards, the atmospheric solids analysis probe mass spectrometry (ASAP-MS) is a powerful ionization sourceforcharacterization of samples in original form. Initially, two methodologies were used to determine the chemical composition of the samples: (1) using a temperature gradient ranging from 150 to 600 °C at a heating rate of 150 °C.min-1(parafina) or 50 °C.min-1; (2) with a constant temperaturearound350 °C. ASAP(+)-MS ionized crude oil and paraffin, showing a typical petroleum profile in the range of m/z200 -1400 for both samples. This performancecould relateASAP sourceto detection of compounds of high molecular weight (> 1000 Da). In addition, the AC standardswere identifiedin two ionicforms: radicals, [M]+•and protonated cations, [M+H]+, with minimal fragmentation. Therefore, ASAP was efficient for accessing the chemical composition of polar and non-polar compounds.Analysis of the Cannabis sativaL. plant, were doing by ultra-high performance liquid chromatography coupled to travelingwave ionic mass spectrometry (UPLC-TWIMS MS) using electrospray ionization source in both modes, ESI (±). Hashish, marijuana, and parts of the plant Cannabis sativaL. (flower and leaf) were analyzed. Isomeric compounds were identified inacomplex mixture of cannabinoids, mainly ?9-THC, cannabidiol (CBN-C5and Mw= 310 Da), ?9-tetrahydrocannabinolic acid A and B (?9-THCA-C5A/B and Mw= 358 Da) and their isomers. Analizes by ESI-TWIMSMS were identified three isomers, m/z315/313, 311, and 357, while a high selectivity was observedin UPLC-ESI-TOF MS data, identifying more thanfour isomeric compounds in the single ion acquisition mode (SIM).In other study, we evaluated the use of a high resolution mobility analyzer coupled to ultra high resolution mass spectrometry for molecular characterization of dissolved organic matter. The main goal wastovalidate the reproducibility of trapped ion mobility spectrometry (TIMS), the range of applicability and possible challenges during routine analysis.TIMS coupledto TOF MS and FT-ICR MS showed similar 18performance and high reproducibility. For the analysis of complex mixtures, both platforms were able to aquiriedthe main characteristics. However, the increase ofchemical complexity at nominal mass level (m/z> 300-350), only TIMS-FT-ICR MS was able to solve the compositional tendencies of lower abundance